Motor Ability Analysis of Basic Volleyball Technical Abilities of Physical Education Students, FKIP Riau Islamic University - Zulrafli, Zulrafli; Fernando, Ricky; Sasmarianto, Sasmarianto; Oktaviandi, Oktaviandi (Indonesian Journal of Sport Management, 2025)
This motor ability acts as the basis of a person's ability. This study looks at the analysis and influence of high and low motor ability on basic volleyball techniques. This study involved 30 randomly selected students who had the best grades after taking volleyball courses. The test used is a motor ability test with a validity coefficient of 0.92 with a series of tests; Wall Pass, Basketball Throw, Broad Jump and 4.sec.seconds. Then the test results are made into 2 groups, namely high and low motor ability test results. Furthermore, the skill test (mastery) of basic techniques which includes passing tests, service tests and specie / attack tests. The results of the study There is a difference in the effect of the ability of basic bolavoli techniques between those with high and low levels of motor ability in Penjaskes students at the Faculty of Teacher Training and Education, Riau Islamic University, where the group of students who have a high level of motor ability is better than the group of students who have a low level of motor ability.